ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH TERHADAP GERAKAN KONTRA NARASI RADIKALISME DI MEDIA NU ONLINE - Sulaiman, Anton; Sauki, M.; Susanto, Joko (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Abstract : This study aims to describe the text analysis used by NU Online media in reporting on radicalism movements, to describe the analysis of text production practices used by NU Online media in reporting on the counter-radicalism narrative movement and to describe the analysis of socio-cultural (macro) practices used by NU Online in reporting. counter-radicalism narrative movement. This study uses a text qualitative research method with the critical discourse analysis approach of Norman Fairclough. The data collection techniques by way of observation, interviews and documentation. Data analysis techniques were carried out using source triangulation. The results of this study indicate that NU Online in countering radicalism narratives uses the principles or values of ahlusnunah wal jamaah. There are three main characteristics of the teachings of ahlussunnah wal jamaah or what we call Aswaja which was always taught by Rasulullah SAW and his companions. NU Online creates educational content, before they access social media they find radical articles, of course we will have a meeting and conduct counter narratives and have authoritative references. Analyzing according to the context and issues in society, we present it with good references, clearly in accordance with Aswaja and Pancasila guidelines. The counter-narrative movement is moment bound and can also use alternative narratives. Namely, narratives that focus on reinforcing positive and unifying ideas.